PULMONARY EDEMA IN PATIENTS WITH INTERSTITIAL PNEUMONIA AND CORONARY HEART DISEASE: RADIOLOGY DIAGNOSTIC (World Bulletin of Public Health, 2024)
Pulmonary edema, a critical complication in emergency medical scenarios, often leads to terminal states and fatalities. This study investigates specific X-ray and computed tomography (CT) signs for the differential diagnosis of hemodynamic and membranogenic pulmonary edema in emergency patients with diverse pathologies
Keywords: pulmonary edema; computed tomography; cardiogenic; non-cardiogenic